2018
DOI: 10.1038/s12276-017-0009-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genomic aberrations associated with lymph node metastasis in diffuse-type gastric cancer

Abstract: Diffuse-type gastric cancer (DGC) is a GC subtype with heterogeneous clinical outcomes. Lymph node metastasis of DGC heralds a dismal progression, which hampers the curative treatment of patients. However, the genomic heterogeneity of DGC remains unknown. To identify genomic variations associated with lymph node metastasis in DGC, we performed whole exome sequencing on 23 cases of DGC and paired non-tumor tissues and compared the mutation profiles according to the presence (N3, n = 13) or absence (N0, n = 10) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 47 publications
1
21
0
1
Order By: Relevance
“…These two subtypes are rarely represented in patients with advanced GAC. Recurrent somatic alterations in TP53, CDH1 and RHOA have been reported in diffuse-type primary GACs 10–14. Most recently, Choi et al demonstrated that CMTM2 plays a role in diffuse-type GAC and lymph node metastases in a small patient cohort 11.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These two subtypes are rarely represented in patients with advanced GAC. Recurrent somatic alterations in TP53, CDH1 and RHOA have been reported in diffuse-type primary GACs 10–14. Most recently, Choi et al demonstrated that CMTM2 plays a role in diffuse-type GAC and lymph node metastases in a small patient cohort 11.…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent somatic alterations in TP53, CDH1 and RHOA have been reported in diffuse-type primary GACs 10–14. Most recently, Choi et al demonstrated that CMTM2 plays a role in diffuse-type GAC and lymph node metastases in a small patient cohort 11. Kurashige et al identified DDR2 as a potential driver gene and novel therapeutic target for those forming PC, by analysing four metastatic cell lines 15.…”
Section: Introductionmentioning
confidence: 99%
“…As a transcription factor, CMTM2 expression was downmodulated in HCC tissues, and low CMTM2 expression was associated with the poor prognosis of HCC patients, suggesting a potential tumor suppressor role of CMTM2 in HCC progression [24]. Moreover, a significant novel mutation at CMTM2 was correlated with lymph node metastasis in diffuse-type gastric cancer (DGC), and CMTM2 overexpression significantly restrained cell proliferation in GC cells [25]. Based on these studies and our above results, we hypothesized that LINC01391 may be partially required for CMTM2 to exert its anti-oncogenic effect in GC.…”
Section: Discussionmentioning
confidence: 99%
“…The association among HER2, MET and FOXP3 expression highlights the role of tissue differentiation in gastric adenocarcinoma [43] and identification of genomic aberrations associated with lymph node metastasis in diffuse-type GC provides profiles of somatic mutations and DNA copy numbers [44]. Likewise, intraperitoneal TAMs are expected to be a promising target in the treatment of peritoneal dissemination in gastric cancer [45].…”
Section: Discussionmentioning
confidence: 99%